Be functional

Algebra Level 5

f ( f ( 1 ) ) = f ( f ( 0 ) ) = 0 f(f(-1)) = f(f(0)) = 0

Consider all monic quadratic polynomials f f which satisfy the above condition. What is the sum of the values of f ( 3 ) f(3) over all of these functions?


The answer is 29.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Patrick Corn
Jun 24, 2015

Let f ( 1 ) = a f(-1) = a and f ( 0 ) = b f(0) = b .

Case 1: a b a \ne b . Then f ( x ) = ( x a ) ( x b ) f(x) = (x-a)(x-b) , and we have ( a + 1 ) ( b + 1 ) = a (a+1)(b+1)=a and a b = b ab=b . So a = 1 a = 1 or b = 0 b = 0 . If b = 0 b = 0 we get a + 1 = a a+1 = a , impossible. If a = 1 a = 1 we get 2 ( b + 1 ) = 1 2(b+1)=1 , so b = 1 / 2 b = -1/2 . So f ( x ) = ( x 1 ) ( x + 1 / 2 ) f(x) = (x-1)(x+1/2) .

Case 2: a = b a = b . Then f ( x ) = ( x a ) ( x c ) f(x) = (x-a)(x-c) for some c c , and we have ( a + 1 ) ( c + 1 ) = a (a+1)(c+1) = a and a c = a ac = a . So c = 1 c = 1 or a = 0 a = 0 . If a = 0 a = 0 we get c + 1 = 0 c+1 = 0 , so c = 1 c = -1 and f ( x ) = x ( x + 1 ) f(x) = x(x+1) . If c = 1 c = 1 we get 2 ( a + 1 ) = a 2(a+1) = a , so a = 2 a = -2 and f ( x ) = ( x + 2 ) ( x 1 ) f(x) = (x+2)(x-1) .

So there are a total of three polynomials in the collection, and the sum of f ( 3 ) f(3) for each of these is 7 + 12 + 10 = 29 7+12+10 = \fbox{29} .

Pranshu Gaba
Jun 24, 2015

Let f ( x ) = x 2 + a x + b f(x) = x^2 + ax + b , then f ( 0 ) = b , f ( 1 ) = 1 a + b f(0) = b, f(-1) = 1- a + b .

f ( f ( 0 ) ) = 0 f ( b ) = 0 b 2 + a b + b = 0 f(f(0)) = 0 \iff f(b) = 0 \iff b^2 + ab + b = 0

b = 0 or b + a + 1 = 0 \implies b = 0 \text{ or } b + a + 1 = 0

Let statement p p be b = 0 “b = 0” and statement q q be b + a + 1 = 0 “b + a + 1 = 0” .


f ( f ( 1 ) ) = 0 \phantom{\iff} f(f(-1)) = 0

f ( 1 a + b ) = 0 \iff f(1 - a + b) = 0

( 1 a + b ) 2 + ( 1 a + b ) a + b = 0 \iff (1- a + b) ^2 + (1 - a + b)a + b = 0

1 + a 2 + b 2 2 a + 2 b 2 a b + a a 2 + a b + b = 0 [ b 2 + a b + b = 0 ] \iff 1 + a^2 + \color{#3D99F6}{b^2} -2a +2b - 2ab + a -a^2 + \color{#3D99F6}{ab + b} =0 ~~~ \color{#3D99F6}{[b^2 + ab + b = 0]}

1 a + 2 b 2 a b = 0 \iff 1- a + 2b - 2ab = 0

( 1 a ) ( 2 b + 1 ) = 0 \iff (1-a)(2b + 1) = 0

a = 1 or b = 1 2 \implies a = 1 \text{ or } b = -\frac{1}{2}

Let statement r r be a = 1 “a = 1” and statement s s be b = 1 2 “b = -\frac{1}{2}” .


We want ( p q ) ( r s ) (p \vee q) \wedge (r \vee s) to be true. This is possible when at least one of p p and q q and at least one of r r and s s are true. All the possible cases are enumerated below. A dash ( ) (-) represents a contradiction.

p q r s a b T F T F 1 0 T F F T T F T T F T T F 1 2 F T F T 1 2 1 2 F T T T T T T F T T F T T T T T \begin{array}{|c|c|c|c|c|c|c|} \hline p & q & r & s && a & b\\ \hline \text{T} & \text{F} & \text{T} & \text{F} && 1 & 0\\ \hline \text{T} & \text{F} & \text{F} & \text{T} && - & -\\ \hline \text{T} & \text{F} & \text{T} & \text{T} && - & -\\ \hline\\ \hline \text{F} & \text{T} & \text{T} & \text{F} && 1 & -2\\ \hline \text{F} & \text{T} & \text{F} & \text{T} && -\frac{1}{2} & -\frac{1}{2}\\ \hline \text{F} & \text{T} & \text{T} & \text{T} && - & -\\ \hline\\ \hline \text{T} & \text{T} & \text{T} & \text{F} && - & -\\ \hline \text{T} & \text{T} & \text{F} & \text{T} && - & -\\ \hline \text{T} & \text{T} & \text{T} & \text{T} && - & -\\ \hline\end{array}

Three ordered pairs of ( a , b ) (a, b) are obtained viz. ( 1 , 0 ) , ( 1 , 2 ) , ( 1 2 , 1 2 ) (1, 0), (1, -2), (\frac{1}{2}, -\frac{1}{2}) . Therefore the three quadratic equations are x 2 + x , x 2 + x 2 , x 2 1 2 x 1 2 x^2 + x, x^2 + x - 2, x^2 -\frac{1}{2}x - \frac{1}{2} .

Substituting x = 3 x =3 gives f ( 3 ) = 12 , 10 , 7 f(3) = 12, 10, 7 respectively.

The sum of all possible values of f ( 3 ) f(3) is 12 + 10 + 7 = 29 12 + 10 + 7 = \boxed{29} . _\square

Moderator note:

The case checking is excessive. You just need 2 × 2 2 \times 2 cases.

IE when checking for b = 0 b = 0 to satisfy the first condition, we do not need to care if b + a + 1 = 0 b+a+1 = 0 or not.

Bill Bell
Jun 23, 2015

Define the quadratic symbolically. Form two expressions representing f ( f ( 1 ) ) f(f(-1)) and f ( f ( 0 ) ) f(f(0)) and pass them to a solver, which will pass pack pairs of solutions for b b and c c , one at a time. For each solution pair, substitute the parameters in the quadratic as well as the value of the indeterminate, x x to obtain the value f ( 3 ) f(3) . Keep running total.

Jason Zou
Jun 29, 2015

We can split this problem into two cases, where f ( 0 ) = 0 f(0)=0 and where f ( 0 ) 0 f(0) \neq 0 .

Case 1: f ( 0 ) = 0 f(0)=0 . We have f ( x ) = x 2 + b x f(x)=x^2+bx . Now f ( 1 ) = 1 b f(-1)=1-b and f ( f ( 1 ) ) = ( 1 b ) 2 + b ( 1 b ) = 1 b f(f(-1))=(1-b)^2+b(1-b)=1-b . Since f ( f ( 1 ) ) = 0 f(f(-1))=0 , 1 b = 0 1-b=0 and b = 1 b=1 giving f ( x ) = x 2 + x f(x)=x^2+x and f ( 3 ) = 12 f(3)=12 .

Case 2: f ( 0 ) 0 f(0) \neq 0 . Let f ( 0 ) = c f(0)=c so f ( c ) = 0 f(c)=0 . Let f ( x ) = x 2 + b x + c f(x)=x^2+bx+c . From Vieta's, the product of the roots is c c , so the other root must be 1 1 , and b = ( c + 1 ) b=-(c+1) . We now have f ( x ) = x 2 ( c + 1 ) x + c f(x)=x^2-(c+1)x+c . Plugging in 1 -1 , we get f ( 1 ) = 2 + 2 c f(-1)=2+2c . Since the only roots are c c and 1 1 , we either have f ( 1 ) = c f(-1)=c or f ( 1 ) = 1 f(-1)=1 . If f ( 1 ) = c f(-1)=c , we get 2 + 2 c = c 2+2c=c and c = 2 c=-2 , giving f ( x ) = x 2 + x 2 f(x)=x^2+x-2 and f ( 3 ) = 10 f(3)=10 . If f ( 1 ) = 1 f(-1)=1 , we get 2 + 2 c = 1 2+2c=1 and c = 1 / 2 c=-1/2 , giving f ( x ) = x 2 x 2 1 2 f(x)=x^2-\frac{x}{2}-\frac{1}{2} and f ( 3 ) = 7 f(3)=7 .

The values of f ( 3 ) f(3) are 7 , 10 , 12 7,10,12 and the sum is 29 \boxed{29} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...